Constructing Workstation Applications: Component Integration Strategies for a Changing Health-Care System - Greenes, R. A.; Deibel, S. R. A. (Yearbook of Medical Informatics, 1996)
A health-care workstation is the means by which a professional interacts with the information artifacts of health care. However, a major transformation is taking place in the software architecture of health-care systems that alters significantly the role of the workstation. Health-care systems are becoming more complex in response to the need to support “extended enterprises” across regions, and provide both horizontal and vertical integration capabilities. Component-based software methodologies are being introduced that match well the needs of these large systems and the component services they must integrate. In the component-based framework, a workstation functions less as a “portal” for information transactions carried out on distant host computers, and more as the “orchestrator” for tasks involved in assembling, organizing, presenting, and manipulating information. Applications residing on workstations access distributed software components that carry out encapsulated functions for the application. Componentintegration methodologies include both formal and ad hoc approaches; the principal emerging technologies are the World Wide Web (WWW), CORBA, Java, OLE, and OpenDoc. An emerging strategy appears to be that of developing application integration environments that encompass and support all of these integration methodologies. Component-based approaches also facilitate standardization at the message level, as messages to classes of components can serve to focus such standardization.
Keywords: Workstations; Integration; WWW; Corba; Java; OLE